Proximate composition, phytochemical screening and anti-hyperglycemic effect of elephant foot yam (Amorphophallus paeoniifolius) tuber on alloxan induced diabetic rats - Rahman, Shaikh Shahinur; Muhsin, Mir Mohammad; Karim, Md. Rezaul; Zubaer, Md.; Rahman, Md. Hafizur; MA. Rouf, Shakh (Progress in Nutrition, 2021)
Summary. Purpose: The objectives of this study were to explore the nutrient analysis of elephant foot yam tuber and also observe the anti-hyperglycemic effect on both diabetic and non-diabetic rats. Methods: Healthy adult Long Evans rats were grouped into four, and each group had six rats. Diabetes was induced intraperitoneally by injecting 140 mg/kg body weight of alloxan dose, and 500 mg/kg bd.wt of Amorphophallus paeoniifolius powder was administered orally for six weeks of both diabetic and non-diabetic experimental rats, and next three weeks supplementary feeding were pulled out. Results: The proximate nutritional composition showed that elephant foot yam is a good source of dietary complex carbohydrate, fiber, minerals such as- calcium, phosphorous, potassium and zinc as well as phytochemicals. This tuber was investigated for the presence of 25 anti-diabetogenic phytochemicals. Among them, 17 phytochemicals were detected in elephant foot yam but eight phytochemicals viz- anthraquinone, carotenoid, cardiac glycoside, glycoside, phlobotanin, phenol, saponin and tannin were not found. Fasting blood glucose (FBG) level was reduced remarkably (p<0.05) in diabetic rats after 1st week and were highly significant (p≤0.001) after 3rd week of experimental feeding. There was no significant change in the FBG levels of normoglycaemic animals. However, FBG was more sustainable even after withdrawn the supplementary feeding diet. Conclusion: Elephant foot yam tuber could be used as a medicinal food for the treatment of diabetes mellitus.